Pisces: an accurate and versatile variant caller for somatic and germline next-generation sequencing data - Dunn, Tamsen (Bioinformatics, 2019)
MOTIVATION: Next-generation sequencing technology is transitioning quickly from research labs to clinical settings. The diagnosis and treatment selection for many acquired and autosomal conditions necessitate a method for accurately detecting somatic and germline variants. RESULTS: We have developed Pisces, a rapid, versatile and accurate small-variant calling suite designed for somatic and germline amplicon sequencing applications. Accuracy is achieved by four distinct modules, each incorporating a number of novel algorithmic strategies. AVAILABILITY AND IMPLEMENTATION: Pisces is distributed under an open source license and can be downloaded from https://github.com/Illumina/Pisces. Pisces is available on the BaseSpace™ SequenceHub. It is distributed on Illumina sequencing platforms such as the MiSeq™ and is included in the Praxis™ Extended RAS Panel test which was recently approved by the FDA. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.